Cuban Labor Reforms in the Mexican Press. Critical Analysis of the Speech of La Jornada and Reforma - Celecia Pérez, Cosette (2019)
Studying the socio-economic transformations promoted in Cuba by the government of Raúl Castro allows us to delve into the remarkable and dynamic transformations that the island has experienced for a decade. This article addresses, from the critical analysis of the discourse, the treatment that the Mexican newspapers La Jornada and Reforma gave to the reduction of jobs positions and the extension of private work in Cuba during the period 2010-2011. The aforementioned methodological design, also supported by interviews, made it possible to identify the way in which power is reproduced in the texts, as well as the mediations of the state control over information in Cuba and the editorial interests of Mexican newspapers, imposed on the process of journalistic construction.